From Ethnographical Subjects to Archaeological Objects: Pierre Loti on Easter Island (Rapa Nui) - Schavelzon Chavin, Daniel Gaston (2014)
In 1872 French sailor Pierre Loti visited the desolate Pacific island of Rapa Nui. Descriptions in his diary and drawings were published and received great public interest. Here were all the ingredients to satisfy nineteenth century ideas of the exotic: remote, tropical, cannibal inhabited, strange rituals and frenzied dancing, and in addition – the ruins of an ancient and unknown civilisation. But Loti had visited the island almost at the end of its occupation by its indigenous people. The large stone statues had not been erect for some time, even though he recorded them as being so, and its population had been decimated. So Loti’s graphic and written descriptions were embellished for his audience, a fact that is almost as interesting as the real fate of Rapa Nui.